The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1186/s12913-017-2258-4
|View full text |Cite
|
Sign up to set email alerts
|

Workplace violence against nurses in the Gambia: mixed methods design

Abstract: BackgroundThe aim of this study was to assess the prevalence, perpetrators and factors associated with workplace violence against nurses in public secondary health care facilities from two health regions in the Gambia.MethodsData was collected from 219 nurses using self-administered questionnaire and 35 face-to-face interviews. The data collection was conducted between July and September 2014 in 14 public secondary health care facilities.ResultsA sizable majority of respondents (62.1%) reported exposure to vio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
84
5
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(118 citation statements)
references
References 20 publications
15
84
5
3
Order By: Relevance
“…Results of gender difference in the prevalence of sexual harassment have been mixed. In some studies, workplaces with higher proportion of females were associated with increased risk of sexual harassment (Boafo et al, ; Celik & Celik, ; Cogin & Fah, ), while opposite findings were also reported (Sisawo, Ouedraogo, & Huang, ; Zeng et al, ). In this meta‐analysis, compared with male nurses, female nurses reported lower prevalence of sexual harassment.…”
Section: Discussionmentioning
confidence: 96%
“…Results of gender difference in the prevalence of sexual harassment have been mixed. In some studies, workplaces with higher proportion of females were associated with increased risk of sexual harassment (Boafo et al, ; Celik & Celik, ; Cogin & Fah, ), while opposite findings were also reported (Sisawo, Ouedraogo, & Huang, ; Zeng et al, ). In this meta‐analysis, compared with male nurses, female nurses reported lower prevalence of sexual harassment.…”
Section: Discussionmentioning
confidence: 96%
“…Several cross sectional surveys have been conducted in various parts of the world, but surprisingly, qualitative (perception) studies have scarcely been performed. 32,33,[41][42][43] The perception of young doctors has remained almost unexplored hitherto. To our knowledge this is the first qualitative study in India which has explored the perception of young (junior) doctors regarding health care work place violence.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] In other parts of the world also, several studies have been conducted. [31][32][33][34][35][36][37] By means of their all India surveys, Indian Medical Association (IMA) have reported that 75% doctors had experienced violence and 82.7% felt stressed out. 3,5,10 Nonetheless, there exits a dearth of qualitative studies on this problem.…”
mentioning
confidence: 99%
“…Four items that are widely used in international studies were used to measure nurse experienced workplace violence (Hanrahan, Kumar, & Aiken, ; Sisawo, Ouédraogo, & Huang, ). Two items were used to measure verbal abuse, and the other two were used to measure physical abuse.…”
Section: Methodsmentioning
confidence: 99%